The Relationship Between Mothers’ Knowledge On Posyandu Services And Their Frequency Of Visit To Posyandu In Karangrejo Village Purworejo Regency - Yustia Rahendra; Luluk Khusnul Dwihestie (JURNAL KEBIDANAN KESTRA (JKK), 2023)
Integrated Service Post (Posyandu) is among the Community-based Health Efforts (UKBM) managed by and for benefits of the community members assisted by health workers’ technical supports. Posyandu is a strategy implemented by the Indonesian government and assigned by the Ministry of Health to conduct early detection of any growth disorders among toddlers, especially stunting (growth failure). However, in reality, the community hardly use Posyandu services due to mother’s lack of knowledge regarding the services. This study was aimed to investigate the relationship between mothers’ knowledge on Posyandu services and their frequency of visit to Posyandu in Karangrejo village, Purworejo regency. The researcher implemented quantitative approach with observational analytic method and cross-sectional research design. The respondents were mothers with 12-59 months aged children in Karangrejo village. There were 44 participants chosen using total sampling technique. Spearman’s rank statistical test revealed that 20 respondents (45.4%) had good knowledge on Posyandu services and therefore frequently visited Posyandu for their toddlers while 5 of them (11.4%) had little knowledge on the services which explained why they did not pay regular visits to Posyandu. Further, the results showed p-value=0.000 and correlation coefficient 0.698 meaning that the relationship of mothers’ knowledge on Posyandu services and their frequency of visit to Posyandu in Karangrejo village, Purworejo regency was considered to be moderate (C=0.698). It is suggested that mothers with children of 12-59 months age regularly visit Posyandu to ensure the good growth of their children.